Ichthyosis Prematurity Syndrome: A Case Report and Review of Known Mutations. Issue 4 (29th May 2014) - Kiely, Clare; Devaney, Deirdre; Fischer, Judith; Lenane, Patricia; Irvine, Alan D.
Abstract Ichthyosis prematurity syndrome (IPS; Mendelian Inheritance in Man 608649) is classified as a syndromic autosomal recessive ichthyosis. Here we describe two siblings with IPS and report a recurrent homozygous mutation (c.1430T>A) that is predicted to lead to a p.Val477Asp substitution in fatty acid transport protein 4. This mutation has arisen for the second time in an entirely distinct population from the Scandinavian population where it was first described.